Environmental history in Central Croatia for the last two millennia - vegetation, fire and hydrological changes under climate and human impact : Dvije tisuće godina okolišnih promjena na području središnje Hrvatske - vegetacija, požari i hidrologija utjecani klimatskim prilikama i ljudskim pritiskom - Hruševar, Dario (Array, 2020)
This paper presents the paleoenvironmental reconstruction of a mire sequence near the village Blatuša, with a focus on changes in vegetation composition, hydrological regime and fire history of the Banovina/Kordun area during the last two millennia. For this purpose, pollen, non-pollen and charcoal analysis were done. By the application of CONISS statistical analysis three different pollen assemblage (sub)zones could have been distinguished: a dominance of alder-beech/oaks from the 2nd to the middle of the 7th century, followed by a prevalence of grasses-beech/oaks till the end of the 13th century. Finally, an assemblage of grasses-hornbeam/oaks populated the area from the 14th to the beginning of the 20th century. The high abundance of peat mosses (Sphagnum) from the 11th to the end of the 14th century must indicate increased precipitation and higher frequencies of rainfall during the Medieval Climate Anomaly. Transition from an ombrotrophic to minerotrophic phase of mire evolution during the Little Ice Age is caused by changing in moisture level, with somewhat wetter period prevailing till the middle of the 17th century followed by drier conditions till the beginning of the 20th century. Although cereal pollen grains first appear from the layers dated to the late 14th century and the proportion of secondary anthropogenic indicators were low during the entire Middle Ages, a large number of charcoal particles suggests stronger anthropogenic activity than indicated by observed changes in vegetation composition. Still, a sharp rise of non-arboreal pollen during the Migration period most likely reflect a general natural succession process on mire surface than persuable proof of Avaric-Slavic impact on vegetation. Direct anthropogenic pressure indicated by weeds and cereal pollen can be tracked from the Late Middle Ages onwards.